Opportunities for Anti-Bias Frameworks in Japanese EFL Textbooks - Kate Efron (Babylonia, 2021)
In Japan, recent Foreign Language Activities (2018-2020) policies have explicated the importance of facilitating multiculturalism and global thinking through education and educational tools, including through the use of textbooks. Accordingly, an Anti-Bias Framework (ABF) is one way for educators to develop learners’ global and cultural identities, as well as learners’ appreciation of human differences. ABFs are of particular relevance in multicultural textbooks and classrooms, as they are used for helping students develop local and international identities, and for helping learners eliminate biases. However, the current EFL textbooks (2018-2020) issued by the Japanese Ministry of Education are not inclusive of ABFs. Consequently, there are numerous missed opportunities for teachers and learners to engage in active anti-bias lessons for the facilitation of global citizenship. This paper seeks to address this gap in the textbooks by discussing opportunities for EFL teachers in Japan (and elsewhere) to use anti-bias frameworks in language and culture education. Elaborating upon the Teaching Tolerance Anti-Bias Framework (2017), this article proposes that EFL students in Japan can develop intercultural competencies and anti-bias thinking through an ABF, and offers suggestions for lesson activities, guided classroom discussions, engagement with local interlocutors, for English language development. While positioned against the backdrop of the Japanese EFL elementary classroom, these suggestions can be adapted to other EFL in-person and online classrooms, as well.